Fostering Flexibility in the New World of Work: A Model of Time-Spatial Job Crafting - Wessels, Christina; Schippers, Michaéla C.; Stegmann, Sebastian; Bakker, Arnold B.; van Baalen, Peter J.; Proper, Karin I. (Frontiers in Psychology, 2019)
In today’s “new world of work”, knowledge workers are often given considerable flexibility regarding where and when to work (i.e. time-spatial flexibility) and this has become a popular approach to redesigning work. Whilst the adoption of such practices is mainly considered a top-down approach to work design, we argue that successful utilization of time-spatial flexibility requires proactivity on the part of the employee in the form of time-spatial job crafting. Previous research has demonstrated that time-spatial flexibility can have both positive and negative effects on well-being, performance, and work-life balance; yet remains mute about the underlying reasons for this and how employees can handle the given flexibility. Drawing on research from work design, we posit that in order for employees to stay well and productive in this context, they need to engage in time-spatial job crafting (i.e. a context-specific form of job crafting that entails reflection on time and place), which can be considered a future work skill. We propose a theoretical model of time-spatial job crafting in which we discuss its components, shed light on its antecedents, and explain how time-spatial job crafting is related to positive work outcomes through a time/spatial-demands fit.